ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA KEPATUHAN PENGOBATAN TUBERKULOSIS SELAMA PANDEMI COVID-19 DI KOTA KENDARI TAHUN 2021 - Emi Andriani; La Ode Muhamad Sety; Hariati Lestari (Endemis Journal, 2022)
Tuberculosis and COVID-19 are infectious diseases, both of which cause respiratory problems. Treatment adherence is interpreted as what is instructed in treatment should be followed properly.The methods in this study use analytical observational research design with a cross sectional approach. The sample in this study is the same as the population of BTA+ pulmonary Tuberculosis patients who re-treat tb and mandatory treatment for 6 months in 2021, as many as 85 people. Because ≥100 then use 10-15% or 20-25% or more of the existing population. Meanwhile, if the population ≤100 all existing populations are sampled (Arikunto, 2014). Because the number of samples in this study ≤100, the sample was taken in total sampling, namely all TB patients as many as 85 people. Statistical test using the Chi Square test. The results showed 85 respondents (100%), respondents with a less compliant category of 49 respondents (57.6%) and respondents with a compliant category of 36 respondents (42.4%), found that there was a meaningful relationship of attitude (p value = 0.000< 0.05), health services (p value = 0,002< 0.05), otherwise there was no meaningful relationship between treatment with OAT (p value = 0.118 > 0.05).